The effect of in vivo T helper and T suppressor lymphocyte depletion on wound healing. - Barbul, A (1989)
The role of T lymphocytes in wound healing is still not well-defined. Because it had been previously shown that in vivo depletion of T cells leads to impaired wound healing, the effect of depleting T cell subsets on subsequent fibroplasia was studied. T helper/effector cells were depleted by the use of the monoclonal antibody GK1.5, reactive against the L3T4 antigen (CD4). T suppressor/cytotoxic lymphocytes were depleted by using the 2.43 monoclonal antibody reactive against the Lyt 2 antigen (CD8). In the first experiment, Balb/c mice were treated with the antibodies starting at 24 hours before wounding was performed, and weekly thereafter. Depletion of the T helper/effector cells had no effect on wound-breaking strength or hydroxyproline deposition in sponge granulomas, whereas depletion of T suppressor/cytotoxic cells significantly enhanced both of these healing parameters. In a second experiment, T cell subset depletion was started on Days 0, 3, 7, 10, and 14 postwounding, and treatments were continued weekly thereafter. Once again, depletion of T helper/effector cells had no effect on wound healing, whereas depletion of T suppressor/cytotoxic cells markedly increased both wound-breaking strength and collagen synthesis. In conclusion, the data show that T suppressor/cytotoxic cells have a counter-regulatory role in wound healing, whereas the T cell subset responsible for up-regulating wound healing remains to be identified.